2019
DOI: 10.1111/psyg.12403
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral inflammatory biomarkers in Alzheimer's disease and mild cognitive impairment: a systematic review and meta‐analysis

Abstract: Background In the past few decades, it has been demonstrated with animal models and clinical studies that a chronic inflammatory process significantly contributes to Alzheimer's disease (AD) pathogenesis. Methods We systematically searched on PubMed and Web of Science for studies associated with peripheral inflammatory biomarkers in AD and mild cognitive impairment (MCI) before July 2018. Meta‐analysis was conducted to summarise results of studies relative to peripheral cytokines and chemokines in AD and MCI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 36 publications
2
46
3
Order By: Relevance
“…Modifications of the concentrations of several cytokines (160)(161)(162)(163)(164) and other inflammatory biomarkers associated with either microglia-e.g., soluble TREM2 (sTREM2), monocyte chemoattractant protein-1 (MCP-1), and YKL-40 (165-168)or astroglia, e.g., YKL-40 (161), are extensively investigated in AD patients. These alterations, potentially, reflect the inflammatory mechanisms within the CNS coupled with the neurodegenerative pathways (11,166).…”
Section: Fluid Biomarkers Of Neuroinflammation In Alzheimer's Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Modifications of the concentrations of several cytokines (160)(161)(162)(163)(164) and other inflammatory biomarkers associated with either microglia-e.g., soluble TREM2 (sTREM2), monocyte chemoattractant protein-1 (MCP-1), and YKL-40 (165-168)or astroglia, e.g., YKL-40 (161), are extensively investigated in AD patients. These alterations, potentially, reflect the inflammatory mechanisms within the CNS coupled with the neurodegenerative pathways (11,166).…”
Section: Fluid Biomarkers Of Neuroinflammation In Alzheimer's Diseasementioning
confidence: 99%
“…The main issue concerning the peripheral measurements of inflammatory biomarkers is that they may not directly reflect brain neuroinflammation (163). Nonetheless, IL-6 and IL-1β concentrations are significantly higher in AD compared to cognitively normal controls in four meta-analysis (160)(161)(162)(163). IL-1β is a key molecule participating in the inflammatory response, cell proliferation, differentiation, and apoptosis.…”
Section: Fluid Biomarkers Of Neuroinflammation In Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with a potentiated trained immunity status of AD innate cells, several authors have reported elevated levels of circulating pro-inflammatory cytokines and amplified inflammatory response of blood cells in AD patients. Despite some inconsistent results, meta-analysis studies confirm an overall trend of increased pro-inflammatory cytokines in AD (82, 83), and higher levels of cytokines were observed in patients with early or mild forms of AD (84, 85). Similarly, peripheral innate cells of AD patients show a “primed” state and the percentage of peripheral monocytes producing pro-inflammatory cytokines increases early in AD (86).…”
Section: Evidence Of Innate Memory Pathways In Admentioning
confidence: 94%
“…Interestingly, patients with AD exhibit elevated peripheral inflammatory cytokine levels very similar to those recorded in patients with MPNs, including elevated C-reactive protein, interleukin-1β (IL-1β), IL-2, IL-6,IL-8, IL-12, IL-18, soluble tumor necrosis factor receptor1 (sTNFR1), soluble tumor necrosis factor receptor2 (sTNFR2), monocyte chemotactic protein-1 (MCP-1), MCP-3, interferon-γ-inducible protein 10, and soluble CD40 ligand. Several of these inflammatory markers have also been found to be elevated in cerebrospinal fluid of patients with AD, including in addition elevated levels of IL-10, transforming growth factor-beta1 (TGFB1), YKL-40, and soluble triggering receptor expressed on myeloid cells2 (TREM2) [52,53].…”
Section: Inflammatory Cytokines Are Elevated and Upregulated In Patiementioning
confidence: 99%